Patient-Community Perspectives on Real-World Evidence: Enhancing Engagement, Understanding, and Trust - Oehrlein, Elisabeth M.; Graff, Jennifer S.; Harris, Jason; Perfetto, Eleanor M. (The patient : patient-centered outcomes research, 2019)
Background Healthcare stakeholders have pronounced both enthusiasm and apprehension over the expanding use of real-world evidence (RWE). The patient community—those who benefit from new treatments but are vulnerable to potential safety risks and whose routine medical encounters are used to generate RWE—has been less vocal. Understanding patient perspectives on the use of RWE to guide clinical decision making and inform regulatory decisions and value assessments is imperative. Methods We convened a day-long, multi-stakeholder roundtable in Washington D.C., USA, on 31 July 2017 to gather patient-community views on RWE and related concerns and the communications, information and tools needed by patients to understand, trust, and use RWE. Participants included a convenience sample of National Health Council (NHC) members primarily representing patient groups as well as non-patient members with an interest in RWE. Participants were organized into small, pre-assigned groups, ensuring representativeness across stakeholders and patient leadership. Discussions, including storyboards, notes, and illustrative examples were captured and later analyzed thematically by NHC staff. Results Ten RWE themes emerged: (1) most patients were unaware of RWE and its actual or potential uses, (2) common definitions for real-world data and RWE are needed, (3) patient organizations need RWE skills and tools, (4) patient–scientist partnerships can help differentiate high-quality RWE, (5) RWE should inform decision making, (6) clinician support is needed for RWE uptake in patient decision making, (7) communications to patients should be balanced and empowering, (8) context of use impacts RWE acceptability/trust, (9) privacy/data ownership require clarity, and (10) patient-generated data are also real-world data (RWD). Conclusion Patients see great possibility in using RWE to understand how a treatment works—to find someone that “looks like me” as assurance of how a treatment might benefit them personally. Patient groups will play a critical role in helping to educate constituents on understanding, contributing to, and using RWE. To maximize patient uptake and the co-development and application of RWE, patient groups require education and tools.